The role of visual cues in mother–pup reunions in a colonially breeding mammal. (1st November 2017) - Wierucka, Kaja; Pitcher, Benjamin J.; Harcourt, Robert; Charrier, Isabelle
Abstract : Parental care is an important factor influencing offspring survival and adult reproductive success in many vertebrates. Parent–offspring recognition ensures care is only directed to filial young, avoiding the costs of misallocated resource transfer. It is essential in colonial mammal species, such as otariids (fur seals and sea lions), in which repeated mother–offspring separations increase the risk of misdirecting maternal effort. Identification of otariid pups by mothers is known to be multi-modal, yet the role of visual cues in this process remains uncertain. We used three-dimensional visual models to investigate the importance of visual cues in maternal recognition of pups in Australian sea lions ( Neophoca cinerea ). We showed that the colour pattern of pup pelage in the absence of any other sensory cues served to attract the attention of females and prompt investigation. Furthermore, females were capable of accurately distinguishing between models imitating the age-class of their own pup and those resembling older or younger age-classes. Our results suggest that visual cues facilitate age-class discrimination of pups by females and so are likely to play an important role in mother–pup reunions and recognition in otariid species.